(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Gladchenko O. Implementation of the interactive teaching methods into the context of forming the informational culture of the future Tax Service specialists. Taking as the basis the synthesis of scientific achievements on the use of interactive methods in the theory and practice of vocational education the author outlines the importance of the implementation of the project method, case method, «Delphi», portfolio, training in small groups, business games in the context of forming the informational culture of the future specialists of the state tax service.